Carteras colectivas en Colombia y las herramientas de medición para la generación de valor (2012)
In the Colombian financial markets, the mutual funds that invest in stocks have obtained in most cases high yields, however, and as demonstrated in this paper, it does not mean always high returns to value. Thus is how a value generation exercise regarding portfolio managers has been conducted for some selected representative mutual funds of the Colombian market. In order to do it two models were used: the Capital Asset Price Model (CAPM) and the three-factor CAPM (Fama - French Model). During the investigation it was apparent that there was no value generation for managed portfolios of four firms recognized in the Colombian market, and no evidence was found that there was the ability to generate alpha (α) during the period of analysis (2006-2011).